Coercion in psychiatric inpatients with psychotic and mood disorders: Associations with trauma history, clinical characteristics, and short-term outcomes - Ergün, Simge; İnce Guliyev, Ezgi (Acta Medica, 2026)
Objectives: Coercive measures are interventions imposed against an individual’s will and may be experienced as traumatic by psychiatric inpatients. This study aimed to examine the association between exposure to coercive measures and trauma burden in psychiatric inpatients, and to investigate the short-term relationship between coercive measures, posttraumatic stress symptoms, and treatment adherence. Methods: The study included 60 patients hospitalized in a psychiatric ward. Trauma burden was assessed using the Childhood Trauma Questionnaire (CTQ) and the Cumulative Trauma Scale (CTS). Perceived social support, illness severity, and functioning were evaluated using standardized clinician-rated and self-report measures. One month after discharge, follow-up interviews were conducted to assess posttraumatic stress symptoms and treatment adherence. Patients exposed to coercive measures were compared with those not exposed. Results: Patients exposed to coercive measures had significantly higher levels of childhood trauma and lifetime cumulative trauma burden. They also demonstrated more severe psychopathology, lower functioning, and lower perceived social support compared to patients not exposed to coercive measures. No significant differences were observed between the groups in posttraumatic stress symptoms or treatment adherence at short-term follow-up. Conclusion: Psychiatric inpatients exposed to coercive measures represent a subgroup characterized by higher trauma burden and greater clinical vulnerability. Assessing trauma history and clinical characteristics may contribute to the identification of patients at increased risk for coercive interventions and support the implementation of trauma-informed care approaches.